Experimental diagenesis using present-day submarine turbidite sands - Bello, Abdulwahab Muhammad; Charlaftis, Dimitrios; Jones, Stuart J.; Gluyas, Jon; Acikalin, Sanem; Cartigny, Matthieu; Al-Ramadan, Khalid (Frontiers in Earth Science, 2022)
Hydrothermal-reactor experiments were conducted to investigate the potential formation of chlorite and microquartz grain coatings on detrital quartz and feldspar grains, and to understand their role in inhibiting the formation of quartz and feldspar (albite) overgrowths. Modern-day proximal and distal unconsolidated sediment from the Bute Inlet (British Columbia, Canada) with known amounts of precursor clay content, were used as starting material. The samples were heated to 250°C at water vapour pressure in a hydrothermal reactor for 72 h. The experiments were performed with and without a silica supersaturated Na2CO3 (0.1 M) solution. Detailed microscopy and EDS mapping analysis identified that the main chlorite precursor, crucial for the formation of the synthesized grain coatings, was a Mg-rich chlorite. The experimental results showed that where the volume of precursor chlorite was low (i.e., 0.1%), notably in the proximal channel Bute samples, chlorite coatings were poorly developed, with a clay volume and maximum chlorite-coating coverage of 0.5% and 47%, respectively. In contrast, with an initial precursor chlorite volume of 14.5%, the distal lobe Bute sample has generated chlorite volume ranging from 42.9% to 56.3% post-experiment, with a maximum chlorite-coating coverage of 77%. The chlorite and microquartz coatings formed in the study are morphologically similar to those seen in natural sandstone reservoirs, and they have restricted the development of quartz and albite cementation in the reactor experiments. The findings provide quantitative data that can be utilised to describe diagenetic changes in mesodiagenetic environments.